High-strength calcium-plastic plate as well as preparation method and application thereof
By using aminopolysiloxane modified polyolefin elastomer and epoxy modified calcium carbonate in calcium plastic sheets, the strength and toughness of calcium plastic sheets have been significantly improved, and the problem of insufficient strength and toughness of existing calcium plastic sheets has been solved.
Patent Information
- Application Number
- CN202411905678.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-23
AI Technical Summary
Due to the addition of high content of lightweight calcium carbonate, the continuity of the polyolefin matrix is reduced, and the strength is difficult to improve, and the toughness is also affected.
The strength and toughness of calcium plastic sheets are significantly improved through chemical crosslinking reactions by using amino polysiloxane modified polyolefin elastomer and epoxy modified calcium carbonate.
It significantly enhances the strength and toughness of calcium-plastic sheets and is suitable for the preparation of packaging boxes with high strength requirements.
Smart Images

Figure BDA0005204324410000041 
Figure BDA0005204324410000051 
Figure BDA0005204324410000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a high-strength calcium plastic plate and a preparation method and application thereof. Background Art
[0002] Calcium plastic board refers to a board made of polyolefin as the base material, with a large amount of light calcium carbonate and a small amount of additives added, and made through plasticizing, hot pressing, foaming and other processes. This board has the characteristics of light weight, sound insulation, heat insulation, moisture resistance, multiple recycling, pressure resistance and wear resistance (10-20 times that of ordinary corrugated paper boxes), and is widely used in the fields of building decoration and packaging materials.
[0003] The patent application document with publication number CN 104295037A discloses a heat-insulating and sound-insulating calcium plastic board, whose substrate layer is composed of the following raw materials in parts by weight: 80-100 parts of high-pressure polyethylene resin, 20-35 parts of light calcium carbonate, 1-2.5 parts of foaming agent, 2.5-4 parts of cross-linking agent, and 2-3.5 parts of wood cellulose. The patent application document with publication number CN 105061864A discloses a LDPE high-foaming calcium plastic board, whose raw materials are: 70-100 parts of LDPE, 1-5 parts of HDPE, 100-120 parts of light calcium carbonate, 7-9 parts of foaming agent, 0.7-0.8 parts of DCP cross-linking agent, 1-2 parts of tribasic lead sulfate, and 2-3 parts of zinc stearate.
[0004] In the existing calcium plastic board composition, the addition of high-content light calcium carbonate leads to a decrease in the continuity of the polyolefin matrix, so its strength is difficult to be further improved. At the same time, the toughness of the polyolefin material itself is slightly poor. After adding high-content light calcium carbonate, its toughness is particularly significantly reduced. The patent application document with publication number CN 115197494A discloses a high-density polyethylene high thermal conductivity composite material, which uses hydroxyl silicone resin to toughen high-density polyethylene, which can reduce the crystallinity of high-density polyethylene. However, in actual application, it is found that the compatibility of hydroxyl silicone resin and polyethylene material is poor, and it is difficult to mix into an ideal uniform phase. Although it can improve the toughness of the material to a certain extent, it will greatly reduce the strength of the material, which is not suitable for application and calcium plastic board products with high strength requirements. Summary of the invention
[0005] In view of the shortcomings and deficiencies of the above prior art, the primary purpose of the present invention is to provide a high-strength calcium plastic board.
[0006] Another object of the present invention is to provide a method for preparing the high-strength calcium plastic sheet.
[0007] Another object of the present invention is to provide application of the above-mentioned high-strength calcium plastic sheet in the preparation of packaging boxes.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A high-strength calcium plastic board comprises the following raw materials in parts by weight:
[0010] 80-100 parts of polyolefin, 20-60 parts of epoxy-modified calcium carbonate, 5-20 parts of aminopolysiloxane-modified polyolefin elastomer, and 1-8 parts of foaming agent;
[0011] The aminopolysiloxane-modified polyolefin elastomer is prepared by the following method:
[0012] (1) heating an aminosilane monomer, a methylsilane monomer and a hydrogen silane end-capping agent to undergo a polymerization reaction under a catalyst condition to obtain a hydrogen-terminated aminopolysiloxane;
[0013] (2) adding hydrogen-terminated aminopolysiloxane and α,ω diene into an organic solvent to dissolve, then adding a hydrosilylation catalyst to carry out a heating copolymerization reaction, and drying and granulating after the reaction is completed to obtain an aminopolysiloxane-modified polyolefin elastomer.
[0014] The polyolefin is preferably polyethylene (PE) or polypropylene (PP).
[0015] The epoxy-modified calcium carbonate is preferably an epoxy-modified calcium carbonate surface-modified with epoxysilane coupling agent KH-560 (γ-glycidyloxypropyltrimethoxysilane) or KH-561 (γ-glycidyloxypropyltriethoxysilane). The surface modification method can be conventional dry surface modification or wet surface modification in the art, which is a commonly used powder surface modification method in the art.
[0016] The foaming agent is preferably one or more of azodicarbonamide, N,N-dinitrosopentamethylenetetramine, sodium bicarbonate, and ammonium bicarbonate.
[0017] The aminosilane monomer in step (1) is preferably one or more of γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane (KBE-902), N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane (KH-602), and N-β-(aminoethyl)-γ-aminopropylmethyldiethoxysilane.
[0018] The methylsilane monomer in step (1) is preferably one or more of octamethylcyclotetrasiloxane (D4), dimethyldimethoxysilane, and dimethyldiethoxysilane.
[0019] The hydrogen silane capping agent in step (1) is preferably one or more of tetramethyldisiloxane (HMM), dimethylmethoxyhydrogensilane, and dimethylethoxyhydrogensilane.
[0020] The amount of aminosilane monomer, methylsilane monomer and hydrogen silane capping agent added in step (1) is controlled so that the weight average molecular weight of the obtained hydrogen-terminated aminopolysiloxane is 500-3000 and the amino group mass percentage is 0.5%-5%.
[0021] The catalyst in step (1) is preferably at least one of sodium hydroxide, potassium hydroxide, sodium siliconate, potassium siliconate, and tetramethylammonium hydroxide; the temperature of the heating polymerization reaction is 80-140° C., and the time is 2-8 hours.
[0022] The α,ω diene in step (2) is preferably one or more of 1,7-octadiene, 1,8-nonadiene, 1,9-decadiene, 1,10-undecadiene and 1,11-dodecadiene.
[0023] The molar ratio of the hydrogen-terminated aminopolysiloxane to the α,ω diene in the step (2) is 1:1-2.
[0024] The organic solvent in step (2) is one or more of isopropanol, ethyl acetate, cyclohexane and petroleum ether.
[0025] The hydrosilylation catalyst in step (2) is chloroplatinic acid isopropanol solution; the temperature of the heating copolymerization reaction is 80-100° C. and the time is 2-8 hours.
[0026] The method for preparing the high-strength calcium plastic sheet comprises the following steps:
[0027] The aminopolysiloxane-modified polyolefin elastomer, epoxy-modified calcium carbonate, polyolefin material and foaming agent are mixed and added into a mixer for uniform mixing, and then extruded into a mold for hot-pressing foaming to obtain a high-strength calcium plastic sheet.
[0028] The application of the above high-strength calcium plastic sheet in the preparation of packaging boxes.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The calcium plastic board of the present invention uses amino polysiloxane modified polyolefin elastomer to modify polyolefin material, and the carbon chain hard segment contained in it can significantly enhance the compatibility and bonding force with polyolefin material, while the polysiloxane chain soft segment contained in it can significantly improve the toughness of the board. Epoxy modified calcium carbonate is further used, which can chemically crosslink with the amino group on the amino polysiloxane modified polyolefin elastomer during the mixing process and the hot pressing foaming process, thereby significantly improving the strength of the board. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0032] Example 1
[0033] A method for preparing a high-strength calcium plastic sheet comprises the following preparation steps:
[0034] (1) γ-aminopropylmethyldiethoxysilane (KBE-902), octamethylcyclotetrasiloxane (D4), tetramethyldisiloxane (HMM) and tetramethylammonium hydroxide catalyst were added into a reaction flask in a mass ratio of 30:70:7:0.05 and stirred to mix evenly. Nitrogen was introduced into the reaction flask for replacement protection. The electric heating mantle was heated to 90° C. and stirred for polymerization for 4 hours. Then the temperature was raised to 140° C. and the catalyst and unreacted raw materials were decomposed under reduced pressure to obtain hydrogen-terminated aminopolysiloxane. The obtained product was tested to have a hydrogen content (Si-H) of 0.11%, an amino content of 2.65%, a theoretical molecular weight of 1818, and a yield of 86%.
[0035] (2) The hydrogen-terminated aminopolysiloxane of step (1) and 1,8-nonadiene in a molar ratio of 1:1.5 are added to a reaction flask containing isopropanol solvent for mixing and dissolving, and nitrogen is introduced into the reaction flask for replacement protection. Then, a 0.01% chloroplatinic acid isopropanol solution catalyst is added, and the electric heating mantle is heated to 90° C. and stirred for polymerization for 4 hours. The active hydrogen reaction of the product is detected to be complete, and the reaction solution is input into a drying granulator for drying and granulation to obtain an aminopolysiloxane-modified polyolefin elastomer.
[0036] (3) Light calcium carbonate is subjected to dry surface modification using 5% epoxy silane coupling agent KH-560 to obtain epoxy-modified calcium carbonate.
[0037] (4) Weigh 100 parts of low-density polyethylene (LDPE), 40 parts of epoxy-modified calcium carbonate of step (3), 10 parts of aminopolysiloxane-modified polyolefin elastomer of step (2), and 4 parts of azodicarbonamide, a foaming agent, and add the mixture to a mixer. Set the processing temperature range to 130-150° C. and mix evenly. Then extrude the mixture into a mold and perform hot pressing and foaming molding at 200-210° C. to obtain a high-strength calcium plastic sheet.
[0038] The results of the mechanical property test (test thickness 2.5 mm) of the high-strength calcium plastic sheet obtained in this example are shown in Table 1 below.
[0039] Table 1
[0040]
[0041] From the results in Table 1, it can be seen that the calcium plastic sheet obtained by the present invention has higher strength and toughness.
[0042] Example 2
[0043] A method for preparing a high-strength calcium plastic sheet comprises the following preparation steps:
[0044] (1) N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane (KH-602), octamethylcyclotetrasiloxane (D4), tetramethyldisiloxane (HMM) and tetramethylammonium hydroxide catalyst were added into a reaction flask in a mass ratio of 40:60:12:0.05 and stirred to mix evenly. Nitrogen was introduced into the reaction flask for replacement protection. The electric heating mantle was heated to 90° C. and stirred for polymerization reaction for 4 hours. Then the temperature was raised to 140° C. and the catalyst and unreacted raw materials were decomposed under reduced pressure to obtain hydrogen-terminated aminopolysiloxane. The obtained product had a hydrogen content of 0.16%, an amino content of 3.20%, a theoretical molecular weight of 1250, and a yield of 83%.
[0045] (2) The hydrogen-terminated aminopolysiloxane of step (1) and 1,7-octadiene in a molar ratio of 1:1.8 are added to a reaction flask containing isopropanol solvent for mixing and dissolving, and nitrogen is introduced into the reaction flask for replacement protection. Then, a 0.01% chloroplatinic acid isopropanol solution catalyst is added, and the electric heating mantle is heated to 90° C. and stirred for polymerization reaction for 4 hours. The active hydrogen reaction of the product is detected to be complete, and the reaction solution is input into a drying granulator for drying and granulation to obtain an aminopolysiloxane-modified polyolefin elastomer.
[0046] (3) Light calcium carbonate is subjected to dry surface modification using 6% epoxy silane coupling agent KH-560 to obtain epoxy-modified calcium carbonate.
[0047] (4) Weigh 100 parts of low-density polyethylene (LDPE), 20 parts of epoxy-modified calcium carbonate of step (3), 5 parts of aminopolysiloxane-modified polyolefin elastomer of step (2), and 4 parts of azodicarbonamide, a foaming agent, and add the mixture to a mixer. Set the processing temperature range to 130-150° C. and mix evenly. Then extrude the mixture into a mold and perform hot pressing and foaming molding at 200-210° C. to obtain a high-strength calcium plastic sheet.
[0048] The results of the mechanical property test (test thickness 2.5 mm) of the high-strength calcium plastic sheet obtained in this example are shown in Table 2 below.
[0049] Table 2
[0050]
[0051] From the results in Table 2, it can be seen that the calcium plastic sheet obtained by the present invention has higher strength and toughness.
[0052] Example 3
[0053] A method for preparing a high-strength calcium plastic sheet comprises the following preparation steps:
[0054] (1) γ-aminopropylmethyldiethoxysilane (KBE-902), octamethylcyclotetrasiloxane (D4), tetramethyldisiloxane (HMM) and tetramethylammonium hydroxide catalyst were added into a reaction flask in a mass ratio of 20:80:5:0.05 and stirred to mix evenly. Nitrogen was introduced into the reaction flask for replacement protection. The electric heating mantle was heated to 90° C. and stirred for polymerization reaction for 4 hours. Then the temperature was raised to 140° C. and the catalyst and unreacted raw materials were decomposed under reduced pressure to obtain hydrogen-terminated aminopolysiloxane. The obtained product had a hydrogen content of 0.07%, an amino content of 1.72%, a theoretical molecular weight of 2857, and a yield of 90%.
[0055] (2) The hydrogen-terminated aminopolysiloxane of step (1) and 1,11-dodecadiene are added to a reaction flask containing isopropanol solvent in a molar ratio of 1:1.1 to mix and dissolve, nitrogen is introduced into the reaction flask for replacement protection, and then a 0.01% chloroplatinic acid isopropanol solution catalyst is added, and the electric heating mantle is heated to 90° C. and stirred for polymerization for 4 hours. The active hydrogen reaction of the product is detected to be complete, and the reaction solution is input into a drying granulator for drying and granulation to obtain an aminopolysiloxane-modified polyolefin elastomer.
[0056] (3) Dry-process surface modification of light calcium carbonate was performed using 4% epoxy silane coupling agent KH-560 to obtain epoxy-modified calcium carbonate.
[0057] (4) Weigh 100 parts of low-density polyethylene (LDPE), 60 parts of epoxy-modified calcium carbonate of step (3), 20 parts of aminopolysiloxane-modified polyolefin elastomer of step (2), and 5 parts of azodicarbonamide, a foaming agent, and add the mixture to a mixer. Set the processing temperature range to 130-150° C. and mix evenly. Then extrude the mixture into a mold and perform hot pressing and foaming molding at 200-210° C. to obtain a high-strength calcium plastic sheet.
[0058] The results of the mechanical property test (test thickness 2.5 mm) of the high-strength calcium plastic sheet obtained in this example are shown in Table 3 below.
[0059] Table 3
[0060]
[0061]
[0062] From the results in Table 3, it can be seen that the calcium plastic sheet obtained by the present invention has higher strength and toughness.
[0063] Comparative Example 1
[0064] A method for preparing a high-strength calcium plastic sheet, compared with Example 1, without adding amino polysiloxane-modified polyolefin elastomer, comprises the following preparation steps:
[0065] 100 parts of low-density polyethylene (LDPE), 40 parts of epoxy-modified calcium carbonate (the same as in Example 1), and 4 parts of azodicarbonamide, a foaming agent, were weighed by weight, mixed, and added to a mixer. The processing temperature range was set to 130-150° C. and mixed evenly. The mixture was then extruded into a mold and hot-pressed and foamed at 200-210° C. to obtain a high-strength calcium-plastic sheet.
[0066] The results of the mechanical property test (test thickness 2.5 mm) of the high-strength calcium plastic board obtained in this comparative example are shown in Table 4 below.
[0067] Table 4
[0068]
[0069] By comparing the results with those of Example 1, it can be seen that the present invention can significantly enhance the strength and toughness of the obtained calcium plastic board by modifying the polyolefin material by adding aminopolysiloxane-modified polyolefin elastomer.
[0070] Comparative Example 2
[0071] A method for preparing a high-strength calcium plastic sheet comprises the following preparation steps:
[0072] (1) Octamethylcyclotetrasiloxane (D4), tetramethyldisiloxane (HMM) and tetramethylammonium hydroxide catalyst were added to a reaction flask in a mass ratio of 100:7:0.05 and stirred to mix evenly. Nitrogen was introduced into the reaction flask for replacement protection. The electric heating mantle was heated to 90° C. and stirred for polymerization reaction for 4 hours. Then the temperature was raised to 140° C. and the catalyst and unreacted raw materials were decomposed under reduced pressure to obtain hydrogen-terminated methyl polysiloxane. The obtained product had a hydrogen content of 0.11%, a theoretical molecular weight of 1818, and a yield of 89%.
[0073] The preparation process of steps (2) to (4) is the same as that of Example 1.
[0074] The results of the mechanical property test (test thickness 2.5 mm) of the high-strength calcium plastic board obtained in this comparative example are shown in Table 5 below.
[0075] Table 5
[0076]
[0077] By comparing the results with those of Example 1 and Comparative Example 1, it can be seen that the use of polysiloxane-modified polyolefin elastomers that do not contain amino groups to modify polyolefin materials can significantly improve the toughness of the resulting calcium plastic board, but the improvement effect on the strength is not significant.
[0078] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A high-strength calcium plastic sheet, characterized in that: The invention comprises the following raw materials in parts by weight: 80-100 parts of polyolefin, 20-60 parts of epoxy-modified calcium carbonate, 5-20 parts of aminopolysiloxane-modified polyolefin elastomer, and 1-8 parts of foaming agent; The aminopolysiloxane-modified polyolefin elastomer is prepared by the following method: (1) heating an aminosilane monomer, a methylsilane monomer and a hydrogen silane end-capping agent to undergo a polymerization reaction under a catalyst condition to obtain a hydrogen-terminated aminopolysiloxane; (2) adding hydrogen-terminated aminopolysiloxane and α,ω diene into an organic solvent to dissolve, then adding a hydrosilylation catalyst to carry out a heating copolymerization reaction, and drying and granulating after the reaction is completed to obtain an aminopolysiloxane-modified polyolefin elastomer.
2. A high-strength calcium plastic sheet according to claim 1, characterized in that: The polyolefin is selected from polyethylene or polypropylene; the epoxy-modified calcium carbonate is selected from epoxy-modified calcium carbonate surface-modified with epoxysilane coupling agent KH-560 or KH-561; the foaming agent is preferably one or more of azodicarbonamide, N,N-dinitrosopentamethylenetetramine, sodium bicarbonate, and ammonium bicarbonate.
3. The high-strength calcium plastic sheet according to claim 1, characterized in that: The aminosilane monomer in step (1) is selected from one or more of γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane and N-β-(aminoethyl)-γ-aminopropylmethyldiethoxysilane.
4. The high-strength calcium plastic sheet according to claim 1, characterized in that: In step (1), the methylsilane monomer is selected from one or more of octamethylcyclotetrasiloxane, dimethyldimethoxysilane, and dimethyldiethoxysilane; and the hydrogen silane capping agent is selected from one or more of tetramethyldisiloxane, dimethylmethoxyhydrogensilane, and dimethylethoxyhydrogensilane.
5. The high-strength calcium plastic sheet according to claim 1, characterized in that: The amount of aminosilane monomer, methylsilane monomer and hydrogen silane capping agent added in step (1) is controlled so that the weight average molecular weight of the obtained hydrogen-terminated aminopolysiloxane is 500-3000 and the amino group mass percentage is 0.5%-5%.
6. The high-strength calcium plastic sheet according to claim 1, characterized in that: The catalyst in step (1) is selected from at least one of sodium hydroxide, potassium hydroxide, sodium silanol, potassium silanol, and tetramethylammonium hydroxide; the temperature of the heating polymerization reaction is 80-140° C., and the time is 2-8 hours.
7. The high-strength calcium plastic sheet according to claim 5, characterized in that: The α,ω diene in step (2) is selected from at least one of 1,7-octadiene, 1,8-nonadiene, 1,9-decadiene, 1,10-undecadiene and 1,11-dodecadiene; and the molar ratio of the hydrogen-terminated aminopolysiloxane to the α,ω diene is 1:1-2.
8. The high-strength calcium plastic sheet according to claim 1, characterized in that: The organic solvent in step (2) is one or more of isopropanol, ethyl acetate, cyclohexane, and petroleum ether; the hydrosilylation catalyst is chloroplatinic acid isopropanol solution; the temperature of the heating copolymerization reaction is 80-100° C., and the time is 2-8 hours.
9. The method for preparing a high-strength calcium plastic sheet according to any one of claims 1 to 8, characterized in that: The method comprises the following preparation steps: The aminopolysiloxane-modified polyolefin elastomer, epoxy-modified calcium carbonate, polyolefin material and foaming agent are mixed and added into a mixer for uniform mixing, and then extruded into a mold for hot-pressing foaming to obtain a high-strength calcium plastic sheet.
10. Use of the high-strength calcium plastic sheet material according to any one of claims 1 to 8 in the preparation of packaging boxes.
Citation Information
Patent Citations
Thermal-insulating sound-insulating calcium-plastic board
CN104295037A
LDPE high-foaming calcium-plastic sheet material
CN105061864A
High-density polyethylene high-thermal-conductivity composite material and preparation method thereof
CN115197494A
Highly-calcium-carbonate-filled highly-resilient soft foamed polyethylene material and preparation method thereof
CN103408823A
Low molecular weight linear amino-terminated silicon oil and synthetic method thereof
CN104262631A